Synthesis and Adsorptive Constitutive Properties of MMS/MFI Materials Prepared on the Basis of Al-Aerosil - K.M. Khomenko; G.I. Zhukow; J.I. Gornikov; R. Leboda; V.V. Brei (Adsorption Science & Technology)
A method for the one-stage bitemplate synthesis of mesoporous zeolite-containing materials based on Al-aerosil (Al-MZ) is proposed. The prepared materials were characterized by IR spectroscopy (FT-IR), X-ray diffraction (XRD) and nitrogen adsorption methods.